Fibrinogen as a Prognostic Predictor in Pediatric Patients with Sepsis: A Database Study. (28th April 2020) - Tang, Xiaomeng; Shao, Lujing; Dou, Jiaying; Zhou, Yiping; Chen, Min; Cui, Yun; Zhang, Yucai; Wang, Chunxia
Abstract : Background . Systemic inflammatory response and vascular endothelial cell injury during sepsis lead to coagulopathy. Fibrinogen has been reported as a biomarker of coagulopathy; however, the prognostic value of fibrinogen remains undefined in pediatric patients with sepsis. The aim of this study was to assess fibrinogen level on pediatric intensive care unit (PICU) admission and to elucidate the relationship between fibrinogen levels and in-hospital mortality in children with sepsis. Methods . We conducted a database study. The sepsis database was divided into a training set (between July 2014 and June 2018) and a validation set (from July 2018 to June 2019). The clinical and laboratory parameters on PICU admission and in-hospital mortality in sepsis database were collected and analyzed. Results . A total of 819 pediatric patients were included from database as a training set. The overall hospital mortality was 12.1% (99/819). The fibrinogen levels were significantly lower in nonsurvivors than survivors. Multivariate logistic regression analysis showed significant associations between fibrinogen, lactate level, and hospital mortality (fibrinogen: odds ratio (OR), 0.767 (95% CI: 0.628-0.937), P = 0.009 ; lactate: OR, 1.346 (95% CI: 1.217-1.489), P < 0.001, respectively), which was confirmed in a validation set (0.616 [95% CI: 0.457-0.829], P = 0.001 ; 1.397 [95% CI: 1.245-1.569], P < 0.001, respectively). The hospital mortality of patients with fibrinogen < 1 g / L, 1-2 g/L, 2-3 g/L, or over 3 g/L displayed an obvious difference (62.5% vs. 27.66% vs. 18.1% vs. 4.2%, respectively). Furthermore, the area under the receiver operating characteristic curve (ROC) for fibrinogen in predicting hospital mortality was 0.780 (95% CI: 0.711-0.850) in pediatric patients with sepsis. Conclusions . Fibrinogen is a valuable prognostic biomarker for pediatric sepsis. The level of fibrinogen lower than 2 g/L on PICU admission is closely related to the greater risk of hospital death in pediatric sepsis.